Bacterial lysis or survival after infection with phage Sf14 depends on combined nutrient and temperature conditions - Nykki D. Ross; Alexis L. Chin; Archana Pannuri; Sarah M. Doore (PLoS ONE, 2025)
Bacteriophage Sf14 is a Moogle-like myovirus that infects Shigella flexneri. S. flexneri is a human pathogen that replicates intracellularly in the intestine, but it persists in a low metabolic state in environmental fresh water sources. Though closely related to FelixO1, Moogleviruses were more recently discovered within the last 10 years; thus, mechanistic knowledge of their infection cycles is still being gathered. This work investigated the combined effects of temperature and nutrient concentration on both host growth and phage replication. In combination, a total of 16 different conditions were analyzed. Results indicate that nutrient-rich media facilitate shorter infection cycles and support phage production at all temperatures. As nutrient content decreased, temperature significantly affected both host cell replication and phage production. Results indicate phage genomes are entering the cells and genes are actively expressed; however, there is a significant delay in expression, which could allow bacterial populations to outpace phage growth.